Intradural rupture of cervical vertebral disc - (:unkn) unknown (My University, 1994)
Study Design. The authors discuss their experience with a patient who had cervical insdurel disc herniation and relate the case to the relevant literature. Objectives, The patient was evaluated with direct radiographies, myeionraphy, alect romyoaraphv, and computerized tomography, as well as with neurologicexamination. The follow-up period was 10 months postoperative. Summary of Background Data. Intradural disc hérniation is a rare pathology neerly always confined to the lumbar region. In 1999, Kalooka et el reviewed the existing literature and discovered 70 cases. Cervical intradural disc herniation, on the other hard. Is much rarer, and there are onty five cases In the literature. Mothods. The petient's neurologic, neuroradiologic, and operative findings were evaluated and compared with the cases reported in the literature. Conclusions. The five patients in the literature had signa of cord compression, but the present patient is the first with:root compression. © 1994, J.B. Lippincott Company.
Keywords: Cervical intradural disc; Intradural disc; Rupture root compression by intradural disc